How NGOs Operationalize the Ecological Capability Approach to Achieve Sustainability Goals - Bañaco, Patrick Elven P. (Archīum Ateneo, 2024)
This study explores how NGOs achieve sustainability goals as they focus on poverty alleviation through ecological capability building. In-depth semi-structured interviews with nine representatives of NGOs working on poverty alleviation were conducted and subjected to thematic analysis within a critical realist perspective. Findings show that the NGOs engage their communities in all the different stages of their programs, creating a sense of empowerment that becomes the foundation for their ecological meta-capability, a holistic approach to the development of human capability that considers social, economic, and environmental aspects. This is better understood by analyzing the interplay of Structure, Agency, and Culture in Archer’s Morphogenetic Approach. The NGO programs are able to initiate social interaction that leads to the community’s agency in growing their capability and attaining a state where they can expand their freedom to make choices for their own sustainable development.